Testing Theories of Change for Dryland Cereals: The HOPE project in central Tanzania 2009-2012 - Orr, Alastair; Muange, Elijah (ICRISAT, 2015)
The Harnessing Opportunities for Productivity Enhancement (HOPE) project was based on a market-led Theory of Change in which farmers adopted new technology for sorghum and millets in response to market demand. This Theory of Change was tested using panel survey data for 360 farm households in central Tanzania covering the crop seasons 2009/10 and 2011/12. Because improved varieties of finger millet were unavailable in 2009, the analysis focused primarily on sorghum. Propensity score matching was used to obtain a matched sample of treatment and control households, which were compared to estimate the unconditional impact of the project, augmented by regression analysis using the matched samples to obtain robust results. HOPE significantly increased the probability of knowing at least one improved sorghum variety by 9.5 %, and the share of farmers adopting improved varieties of sorghum by 13.2 %. However, HOPE had no significant positive impact on the area, yield, and output of sorghum, or improve farmers’ technical efficiency in producing sorghum. HOPE did not increase the use of commercial channels for the supply of improved seed. Finally, HOPE increased neither the commercialization of sorghum, which remained primarily a food crop, nor of finger millet, which was already a cash crop before the start of the project. These findings show that enhancing productivity for dryland cereals requires not just improved varieties but also improved crop management, and that adoption of improved varieties is not driven exclusively by market demand but by the need for household food security. These findings also challenge the relevance of a universal Theory of Change for dryland cereals in Eastern and Southern Africa. Finally, they highlight the need for a revised Theory of Change that reflects the diversity of farmers’ objectives in growing these crops and of market opportunities within the region.
Keywords: Impact analysis; Theory of change; Commercialisation; Sorghum; Millets